DESAIN LEAD RUBBER BEARING PADA PERENCANAAN GEDUNG RUMAH SAKIT “X” DI KOTA PADANG DENGAN LAYOUT MEMANJANG - Shandy, Fara Dilla; Yusmar, Fajri (Teknik Sipil Universitas Negeri Padang, 2024)
A hospital is a vital building with high sensitivity to external disturbances due to its structural vulnerability to damage caused by external factors such as natural disasters, especially earthquakes. Padang, a city located near the Sumatra Fault Zone, is an area with a high seismic risk. Additionally, the building under study is affected by irregularity due to land constraints, resulting in an elongated layout that is susceptible to torque. Furthermore, buildings with a rectangular configuration have different stiffness and inertia along each axis, which can lead to varying structural responses to lateral loads such as wind and earthquakes. The geometry of the structure also influences the magnitude of stiffness and inertia, causing variations in the earthquake loads experienced. This research aims to design a Lead Rubber Bearing (LRB) isolator for the planning of the